STRATEGI GURU DALAM MENINGKATKAN HEALTHY LIFESTYLE MELALUI PROGRAM LITERASI HIDUP SEHAT - Edwita; Uswatun Hasanah (Jurnal Pendidikan Dasar, 2019)
Abstract: Healthy lifestyle is a behavior related to the efforts or activities of a person to maintain and improve their health. This behavior is very important to be instilled since elementary school age. This research aims to improve healthy lifestyle through a healthy living literacy program. This research method in the form of classroom action research, planning procedures, implementation, observation and reflection. The subject of the research development was the first grade students of SDN Rawamangun 05, East Jakarta. The study was conducted in two cycles with the result that the first cycle was 71.35% and the second cycle was 95.88%. It can be concluded that the healthy living literacy program can improve healthy lifestyle in class I students of SDN Rawamangun 05, East Jakarta. Keywords : healthy lifestyle , healthy life literacy program